Simulating vertical excitation energies of solvated dyes: From continuum to polarizable discrete modeling. Issue 1 (31st July 2018) - Giovannini, Tommaso; Macchiagodena, Marina; Ambrosetti, Matteo; Puglisi, Alessandra; Lafiosca, Piero; Lo Gerfo, Giulia; Egidi, Franco; Cappelli, Chiara
Abstract : We present a computational study on the spectroscopic properties of UV‐Vis absorbing dyes in water solution. We model the solvation environment by using both continuum and discrete models, with and without polarization, to establish how the physical and chemical properties of the solute–solvent interaction may affect the spectroscopic response of aqueous systems. Seven different compounds were chosen, representing different classes of organic molecules. The classical atomistic description of the solvent molecules was enriched with polarization effects treated by means of the fluctuating charges (FQ) model, propagated to the first‐order response function of the quantum‐mechanical (QM) solute to include its effects withing the modeling of the electronic excitations of the systems. Results obtained with the QM/FQ model were compared with those from continuum solvation models as well as nonpolarizable atomistic models, and then confronted with the experimental values to determine the accuracy that can be expected with each level of theory. Moreover, a thorough structural analysis using molecular dynamics simulations is provided for each system. Abstract : Continuum PCM and discrete QM/MM solvation methodologies (also including polarization effects modeled by means of a fluctuating charge approach) are challenged to reproduce excitation energies of seven organic dyes in aqueous solution.